Diagnostics and Multi-criteria Analysis of Methods for Drying Buildings After Flooding. Case Study - Ksit, Barbara; Szymczak-Graczyk, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents guidelines for moisture and mycological diagnosis procedures for buildings after flooding. This paper proposes a division of the diagnostic procedure according to the medium of action and collects and presents methods for drying building elements. 54 companies dealing with drying were analyzed. The task of dehumidification is to use various methods to reduce the moisture level of building partitions to the equilibrium moisture level.
Keywords: moisture diagnosis; mycological diagnosis; drying methods; restoration work; flooding